Association between subfoveal choroidal thickness and leakage site on fluorescein angiography in Behçet’s uveitis - Shirahama, Shintaro (Sci Rep, 2019)
This study aimed to clarify the association between the retinal leakage site on fluorescein angiography (FA) and subfoveal choroidal thickness (SCT) measured using enhanced depth imaging optical coherence tomography (EDI-OCT). Twenty-two patients with Behçet’s uveitis were retrospectively selected in this study. They underwent EDI-OCT and FA in both the active and convalescent phases. The associations of the changes between the active and convalescent phases in SCT and in FA leakage in various retinal areas (total retina, peripheral retina, macula, and optic disc) were examined. The changing rates of SCT between the two investigated phases were significantly associated with the changes in total FA leakage scores (y = 1.79X+ 11.7, r(2) = 0.210, p < 0.05). Furthermore, the changes in FA leakage scores in the macula were correlated with the changing rates in SCT (y = 3.72X+ 13.9, r(2) = 0.219, p < 0.05). By contrast, there were no significant associations between the changes in SCT and those in leakage from the peripheral retina or the optic disc on FA. These findings demonstrate that SCT may reflect macular vasculitis as determined using FA, and SCT measurement could be a non-invasive method to investigate inflammation near the macula in Behçet’s uveitis.